Biochemical parameters and oxidative stress markers in Tunisian patients with periodontal disease - Ahmed Gharbi; Ali Hamila; Adel Bouguezzi; Azza Dandana; Salima Ferchichi; Fatiha Chandad; Leila Guezguez; Abdelhedi Miled (BMC, 2019)
Abstract Background Oxidative stress is involved in many diseases including diabetes and cancer. Numbers of studies have suggested its involvement in the pathogenesis of periodontal diseases. The aim of this study was to evaluate the levels of biochemical parameters and oxidative stress markers in plasma of healthy and chronic periodontitis patients. Methods One hundred thirty subjects were divided into two groups; patients (mean age = 42 ± 13.6 y.o) and control (mean age = 44.8 ± 12.6 y.o). Patients and healthy subjects were free from any infection, coronary or heart disease, diabetes or liver failure. Total cholesterol, LDLc, HDLc, Triglycerides (TG), creatinine, uric acid (UA), glucose and urea levels as well as the activities of enzymatic antioxidants such as catalase, glutathione reductase (GR) and total antioxidant capacity (TAOC), were measured in plasma samples using colorimetric assays. Statistical differences between groups were determined by Student's t-test and p ≤ 0.05 was considered as significant. Results Periodontitis patients exhibited significant decrease in the activities of catalase, TAOC, GR and TG, cholesterol, LDLc, glucose, HDLc, uric acid levels in plasma samples in comparison with healthy subjects. However, no statistically significant differences in the levels of creatinine and urea were observed between the two groups. Conclusion The reduction of plasma antioxidant activities (Catalase, TAOC, GR) may have a role in the pathogenesis of periodontal diseases. Our findings suggest a decrease in the host capacity to control the damage caused by oxidative stress. Therefore, therapeutic strategies, aiming at modulating the oxidative stress could be considered as potential tools for the prevention or treatment of periodontal diseases and their potential systemic effects on the general health.